2020
DOI: 10.3340/jkns.2019.0082
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of P2Y12 Reactive Unit to Predict the Periprocedural Thromboembolic and Hemorrhagic Complications According to Clopidogrel Responsiveness and Safety of Modification of Dual Antiplatelet Therapy : A Meta-Analysis

Abstract: The efficacy of P2Y12 reaction unit (PRU) of VerifyNow still remains as a controversial issue in neurointervention. So we investigated the usefulness of PRU of VerifyNow to predict the peri-procedural thromboembolic events (TE) and hemorrhagic events (HE). And we evaluated the safety of modified dual antiplatelet therapy (DAPT) or triple antiplatelet therapy (TAPT) for clopidogrel hyporesponders. We searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, Web of Science and Scopus on Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…There are some methods to measure platelet functions, VerifyNow being one of the major point of care platelet reactivity analysis tools and employed on large clinical trials [14,15]. Some studies have shown an association of hyper-responders to clopidogrel hemorrhagic events while hypo-responders are associated with thrombotic events, although a clear cutoff value has not been de ned for neuroendovascular treatments and this value differed among studies [16][17][18][19][20][21]. Based on the ACCF/AHA 2011 guideline [8], we de ned 208 as cutoff value and investigated hemorrhagic and thrombotic events both in the acute and delayed phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some methods to measure platelet functions, VerifyNow being one of the major point of care platelet reactivity analysis tools and employed on large clinical trials [14,15]. Some studies have shown an association of hyper-responders to clopidogrel hemorrhagic events while hypo-responders are associated with thrombotic events, although a clear cutoff value has not been de ned for neuroendovascular treatments and this value differed among studies [16][17][18][19][20][21]. Based on the ACCF/AHA 2011 guideline [8], we de ned 208 as cutoff value and investigated hemorrhagic and thrombotic events both in the acute and delayed phase.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies of stent assisted coiling reported an association of hemorrhagic and thrombotic events with PRU values in the acute phase [17][18][19][20][21], there are few studies of association between platelet reactivity and these events in the delayed phase after stent assisted coiling. Goh et al reported that evaluating hemorrhagic events up to 6 weeks after endovascular stenting treatment indicated that patients with > 72% PRU inhibition had more major bleeding than those with PRU < 72% [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies of stent assisted coiling reported an association of hemorrhagic and thrombotic events with PRU values in the acute phase [ 17 21 ], there are few studies of an association between platelet reactivity and these events in the delayed phase after stent assisted coiling. Goh et al reported that evaluating hemorrhagic events up to 6 weeks after endovascular stenting treatment indicated that patients with > 72% PRU inhibition had more major bleeding than those with PRU < 72% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higashiguchi et al indicated that personalized dual antiplatelet therapy based on a platelet reaction unit (PRU) cutoff value of 240 significantly reduced thromboembolic complications without increasing hemorrhagic complications [ 17 ] during the endovascular period. However, limited information exists regarding the efficacy of antiplatelet modification based on the Verifynow P2Y 12 platelet function test [ 18 ]. Therefore, the aim of our study was to investigate the clinical outcomes associated with platelet function test-guided clopidogrel modification in patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%